(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2013)
The Purpose of this study is mainly to improve the competitive position of products economic units using technique target cost and method reverse engineering and through the application of technique and style on one of the public sector companies (general company for vegetable oils) which are important in the detection of prices accepted in the market for items similar products and processing the problem of high cost which attract managerial and technical leadership to the weakness that need to be improved through the introduction of new innovative solutions which make appropriate change to satisfy the needs of consumers in a cheaper way to affect the decisions of private customer to buy , especially of purchase private economic units to a series of challenges and changes imposed on who wants to continue looking at the product from the point of view of the customer and adapt to these changes is the adoption of the entrances and strategic cost management techniques.